2012
DOI: 10.2134/agronj2011.0269
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Rolling Effects on Anthracnose of Annual Bluegrass Putting Greens

Abstract: Lightweight rolling can be eff ectively used to increase ball roll distance (BRD) and infl uence anthracnose development on annual bluegrass (ABG) [Poa annua L. f. reptans (Hausskn) T. Koyama] putting green turf. Th e objective of this 3-yr fi eld trial was to evaluate the infl uence of roller type (i.e., sidewinder, triplex mounted vibratory, and nonrolled) and location (center or perimeter) of equipment traffi c on anthracnose severity, turf quality, and BRD of ABG turf maintained at 3.2 mm. Both roller type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…[6][16]). For most of the 20 th century, C. cereale was considered conspecific with C. graminicola , the fungus responsible for maize anthracnose disease, based on morphological similarities [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][16]). For most of the 20 th century, C. cereale was considered conspecific with C. graminicola , the fungus responsible for maize anthracnose disease, based on morphological similarities [17].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of C. cereale as one of the primary diseases impacting turfgrass health on golf course putting greens has prompted several investigations in recent years pertaining to the identity of the fungus, the structure of populations, and the management factors that influence the development of disease in turfgrass hosts ( e.g. [6] [16] ). For most of the 20 th century, C. cereale was considered conspecific with C. graminicola , the fungus responsible for maize anthracnose disease, based on morphological similarities [17] .…”
Section: Introductionmentioning
confidence: 99%
“…In the mid-1990s, researchers discovered that rolling at a frequency of three times weekly reduced dollar spot, and localized dry spot, moss, and broadleaf weeds in creeping bentgrass (Nikolai et al, 2001). Inguagiato et al (2009) observed that rolling decreased the severity of anthracnose (Colletotrichum cereale), whereas Roberts et al (2012) reported that rolling not only increased ball roll distance, but also reduced anthracnose in annual bluegrass putting greens. These experiments demonstrated that turfgrass edaphic environment and pathogen activity could be affected by rolling practices.…”
mentioning
confidence: 99%